Neuropeptide deficient mice have attenuated nociceptive, vascular, and inflammatory changes in a tibia fracture model of complex regional pain syndrome - Guo Tian-Zhi; Wei Tzuping; Shi Xiaoyou; Li Wen-Wu; Hou Saiyun; Wang Liping; Tsujikawa Kazutake; Rice Kenner C; Cheng Kejun; Clark David J; Kingery Wade S (SAGE Publishing, 2012)
Abstract Background Distal limb fracture in man can induce a complex regional pain syndrome (CRPS) with pain, warmth, edema, and cutaneous inflammation. In the present study substance P (SP, Tac1−/−) and CGRP receptor (RAMP1−/−) deficient mice were used to investigate the contribution of neuropeptide signaling to CRPS-like changes in a tibia fracture mouse model. Wildtype, Tac1−/−, and RAMP1−/− mice underwent tibia fracture and casting for 3 weeks, then the cast was removed and hindpaw mechanical allodynia, unweighting, warmth, and edema were tested over time. Hindpaw skin was collected at 3 weeks post-fracture for immunoassay and femurs were collected for micro-CT analysis. Results Wildtype mice developed hindpaw allodynia, unweighting, warmth, and edema at 3 weeks post-fracture, but in the Tac1−/− fracture mice allodynia and unweighting were attenuated and there was no warmth and edema. RAMP1−/− fracture mice had a similar presentation, except there was no reduction in hindpaw edema. Hindpaw skin TNFα, IL-1β, IL-6 and NGF levels were up-regulated in wildtype fracture mice at 3 weeks post-fracture, but in the Tac1−/− and RAMP1−/− fracture mice only IL-6 was increased. The epidermal keratinocytes were the cellular source for these inflammatory mediators. An IL-6 receptor antagonist partially reversed post-fracture pain behaviors in wildtype mice. Conclusions In conclusion, both SP and CGRP are critical neuropeptide mediators for the pain behaviors, vascular abnormalities, and up-regulated innate immune responses observed in the fracture hindlimb. We postulate that the residual pain behaviors observed in the Tac1−/− and RAMP1−/− fracture mice are attributable to the increased IL-6 levels observed in the hindpaw skin after fracture.